Peran Psikologi dalam Pendidikan Islam - Rohimah, Siti; Sugiyarti, Sri; Sanusi, M. (AHKAM, 2024)
This article discusses the role and application of psychology in Islamic education. The aim is to find out the extent of psychology's role in Islamic education, as well as its application in the Islamic education process. This research uses a literature review approach from several book sources, journal articles and websites. The research results show that psychology plays an active role as a means of bridging educators in knowing the character, attitudes, characteristics and habits of students, so that the learning process in education can run smoothly. All obstacles can be resolved precisely and quickly. Understanding the Islamic religion in a kaffah way is an important aspect that must be considered by all pillars of education, such as: school principals, educators, students, parents and all school residents. With a balance between Islamic religious knowledge, then combined with strengthening psychological knowledge, it will have various positive impacts on Islamic religious education it self.